Vascular endothelial growth factor improves the cognitive decline of Alzheimer's disease via concurrently inducing the expression of ADAM10 and reducing the expression of β-site APP cleaving enzyme 1 in Tg2576 mice. (May 2019) - Guo, Hongwei; Xia, Deyu; Liao, Shaohua; Niu, Bing; Tang, Jigang; Hu, Huaiqiang; Qian, Hairong; Cao, Bingzhen
Graphical abstract: Highlights: The production of VEGF was downregulated in the brains of Tg2576 mice. The restoration of VEGF increased the expression of ADAM10 invivo . Elevating the levels of VEGF decreased the expression of BACE1 invivo . Induction of ADAM10 and reduction of BACE1 antagonized Aβ aggregation Tg2576 mice. By decreasing the deposit of Aβ, VEGF improved the cognitive decline of Tg2576 mice. Abstract: Alzheimer's disease (AD) is primarily characterized by the production and deposit of β-amyloid protein (Aβ) in β-amyloid plaques (APs). On this basis, we investigated whether vascular endothelial growth factor (VEGF), a growth factor with important neuroprotective activity, may provide a therapeutic opportunity for treating AD. We initially found that the expression and production of VEGF was downregulated in the brains of Tg2576 mice during the course of AD development and progression. Restoring VEGF in the brains of Tg2576 mice antagonized the production and deposit of Aβ in Tg2576 mice. The addition of VEGF concurrently increased the expression of disintegrin and metalloproteinase domain-containing protein 10 (ADAM10) and decreased the expression of β-site APP cleaving enzyme 1 (BACE1), which contributes to the enhanced clearance of Aβ in vivo . By decreasing the production and deposit of Aβ, VEGF improved the cognitive decline of Tg2576 mice. These observations provide a novel implication for VEGF as a therapeutic approach for the treatment of AD.